Peningkatan Kualitas Lulusan Prodi Magister Ilmu Agama Islam Pascasarjana UIN Ar-Raniry dalam Perspektif Pengguna Lulusan (User) dan Alumni - Salman Abdul Muthallib; Nisa Khairuni; Muhammad Syauqi (DAYAH: Journal of Islamic Education, 2019)
The Department of Islamic Studies is the oldest master’s degree department in postgraduate program of Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia. It has several fields including Islamic Law, Islamic Education, Islamic Economics, Islamic Da’wa, Islamic History and Civilization, etc. In line with the new regulation published by the Ministry of Research and Technology and Higher Education of Republic Indonesia, particularly in relationship with the implementation of the national qualification framework and the national standard of higher education, this department must be driven to fit this regulation. This study took place in three Aceh Province districts including Banda Aceh, Lhokseumawe and Aceh Tengah. The total number of research participants were 17 people consisted of alumni and users. The research found that most participants argued the curriculum of this department must be refined according to the demands of the industrial revolution era 4.0 which requires universities to apply the Indonesian National Qualifications Framework curriculum, particularly on aspects of strengthening foreign languages and the use of information and communication technology.